y 3 2 x 3 Now we use the sum of two cubes formula for the first factor and the

Y 3 2 x 3 now we use the sum of two cubes formula for

This preview shows page 24 - 26 out of 32 pages.

( y 3 ) 2 = ( x 3 + Now we use the sum of two cubes formula for the first factor and the difference of two cubes formula for the second factor. x 3 + y 3 = ( x + y )( x 2 x 3 y 3 = ( x y )( x 2 Hence, x 6 y 6 = ( x + y )( x 2 xy + y 2 ) Student Practice 12 Factor. 64 a 6 1 A-34A-35 Page 24 of 32 Print | Beginning & Intermediate Algebra 1/31/2014 ;...
Image of page 24